Genetic diversity and morphological variation of Pinus gerardiana along the environmental gradient from Zhob, Balochistan, Pakistan - Janat Gul; Shazia Saeed; Alia Ahmed; saad ullah khan Laghari; Abdul Basit; Abdul Rehman; muhammad zahid (Smujo International, 2021)
Abstract. Gul J, Saeed S, Ahmed A, Leghari SK, Basit A, Rehman A, Khan MZ. 2021. Genetic diversity and morphological variation of Pinus gerardiana along the environmental gradient from Zhob, Balochistan, Pakistan. Nusantara Bioscience 13: 121-128. Pinus gerardiana, an evergreen gymnosperm, is an economically- and ecologically valuable tree found in the Takhte Suleman Mountain Range, Zhob northeastern edge of the Balochistan, Pakistan. The present study is based on the assessment of the impact of environmental gradients with special reference to altitudinal gradient and soil variables on morphological, phytochemicals and genetic variation of P. gerardiana. A total of 27 genotypes of P. gerardiana were collected from the three elevation zones ranging from 2000 - 3500 m above sea level. The genetic diversity was assessed by combined markers, the random amplified polymorphic DNA (RAPD) and the Inter Simple Sequence Repeat (ISSR). Polymorphic bands analyzed the data to generate a dendrogram, based on the unweighted pair group method with arithmetic mean (UPGMA). Morphological characters assessed the morphological characters. Phytochemicals were investigated; the total phenolic content and total flavonoid contents were estimated and compared amongst all accessions. Our results revealed variations along altitudinal gradients and related to soil characteristics. The populations at the Middle altitude zone have greater diversity than populations at lower and higher altitudes. The resulting altitudinal variation can be attributed to various geographical and environmental conditions. These results can help in conservation and cultivation of this economically important tree.